PELATIHAN PEMBUATAN BAHAN BAKAR BRIKET AMPAS SAGU SEBAGAI ALTERNATIF ENERGI DALAM SKALA RUMAH TANGGA DI DISTRIK SENTANI TIMUR - Elisabeth V. Wambrauw; Agustinus Agustinus; Elisabeth P. Allo; Lisa Agnesari (JURNAL PENGABDIAN PAPUA, 2017)
Sago Palm is one of staple food source in Papuan. Beside its potential as indigenous food source, other part of the plant can be used as material of house, bridge and other constructed works. However, there is an environmental issues if the residual material from extracting of the starchy from Sago Palm is unmanageable. To solve the issue, this residue can be produced as briquette into a household scale or home industrial scale to empower the community. As known that, the briquette is an alternative energy that can made from rice husk, coals, coconut shell and dregs of sago (residue after extraction process) which those have carbonised or combusted in a certain circumstance. The choice of the raw material of the briquette depends on the local area. Thus the purpose of this community services of the university was to train the local to increase the economical values of dregs of sago and to develop an alternative energy. At the first planning, the event was only taken a place in a villages called Nolokla Village, but because of a reason that changed the location in the Sentani Timur District. The reason was to widen the audiences. The training was done a full day, and the people followed the process with enthusiastic. The participants came from several villages of the district. The local government and participants hope the event can be conducted in future and the collaboration between the university and the community should be increased.Keywords: briquette, dregs of sago, Sentani Timur, community services